Therapeutic Uses of False Sesame (Ceratotheca sesamoides Endl.) in the Sudanian and Sudano-Sahelian Part of Burkina Faso - , Dramane KABORE; , Pingawindé SAWADOGO; , Renan Ernest TRAORE (Archives of Current Research International, 2025)
This study investigates the ethnomedicinal knowledge of false sesame (Ceratotheca sesamoides Endl.) among rural populations in Burkina Faso, with a focus on how this knowledge varies across social parameters such as ethnicity, gender, and age. The primary objective is to assess the extent and distribution of local knowledge concerning the medicinal uses of this underutilized plant, particularly regarding ailments for which it is used as a remedy. The study specifically examines the plant parts employed for therapeutic purposes and the variations in knowledge among different demographic groups. Data were collected through semi-structured ethnobotanical interviews conducted with 240 participants representing 12 distinct ethnic groups. Quantitative analyses were performed using use indices, Shannon diversity indices, and Chi-square tests to identify significant patterns of knowledge distribution. The results showed that gender and age significantly affected knowledge about the medicinal uses of false sesame (p = 0.034 and p = 0.004, respectively), while ethnicity did not have a significant effect. However, the Shannon indices demonstrated a high diversity of knowledge across all demographic groups, indicating a widespread and rich ethnomedicinal understanding of this plant. These findings highlight the importance of preserving traditional knowledge and suggest that false sesame holds potential for contributing to sustainable health care solutions and ethnopharmacological research in areas where access to modern medicine is limited.